Kontribusi Pola Asuh Terhadap Tingkat Resiliensi Akademik Mahasiswa Di Era Digital - Kelly, Estalita (Sultan Idris Journal of Psychology and Education, 2025)
The development of digital technology has brought major changes to the world of higher education. Students are not only required to be able to master lecture materials, but must also be able to adapt to technology-based learning systems. In the midst of easy access to information and flexible study time, new, more complex challenges have emerged. Academic pressures such as heavy workloads, demands to always be responsive online, distractions from social media, to increasingly tight competition often trigger stress, anxiety, and mental fatigue. In such situations, students are required to have the ability to survive, rise, and adapt in the face of pressure and difficulties during the study process. One important factor that forms academic resilience is parenting. The purpose of this study was to analyze the effect of parenting on students' academic resilience. The study used a quantitative approach. A sample of 202 students was taken using the convenience sampling technique. The research instrument used an academic resilience scale and a parenting scale. The results explain that there is a significant influence of authoritative parenting and permissive parenting on students' academic resilience. Meanwhile, authoritarian parenting and neglected parenting do not affect students' academic resilience.